السمات الشخصية والاخلاقية والمهنية(معرفية وأكاديمية وتعليمية) اللازمة لمعلم مدرسة الجودة والتميز (دراسة تطبيقية ) - بشاطة, منير; باشيوة, حسين; يحياوي, عبد الكريم (جامعة الوادي - University of Eloued, 2022)
هدفت هذه الدراسة لمعرفة السمات الشخصية والاخلاقية والمهنية (معرفية وأكاديمية وتعليمية) اللازمة لمعلم مدرسة الجودة والتميز من وجهة نظر المعلمين العاملين بمدارس التعليم الابتدائي بمدينة سطيف للعام الدراسي (2020/2021)، ولجمع البيانات تم الاعتماد على المهج الوصفي التحليلي تماشيا مع طبيعة الموضوع، كما تم اختيار عينة عشوائية بلغ عددها(90) منهم (36) معلم و(54) معلمة، تم الاعتماد على الاستبيان من اعداد الباحث يتكون الجزء الاول من (27 بند) ويشمل الصفات الشخصية (7فقرات) الصفات المهنية(6 فقرات) الصفات الأخلاقية(9 فقرات)،و الجزء الثاني السبل الكفيلة لتنمية وتطوير هذه الصفات (5 فقرات). بعد قياس الخصائص السيكومترية عن طريق صدق الاتساق الداخلي، والثبات بمعامل الفاكرونباخ ، وبعد تحليل البيانات توصلت الدراسة الى النتائج التالية: - أن أفراد الدراسة موافقون على الصفات (الشخصية، الاخلاقية ، المهنية) المرغوبة في معلم مدرسة الجودة والتميز . الكلمات المفتاحية: الصفات الشخصية، الصفات المهنية، الصفات الأخلاقية معلم مدرسة الجودة. Abstract: This study aimed to find out the desired personal, professional and ethical qualities in the teacher of the School of Quality and Excellence from the point of view of teachers working in elementary schools in the city of Setif for the academic year (2020/2021). To collect data, the descriptive and analytical curriculum was used, and a random sample was selected. (100) male and female teachers, a questionnaire was built consisting of (27 items) and includes personal characteristics (7 paragraphs), professional qualities (6 paragraphs), moral qualities (9 paragraphs), and ways to develop these characteristics (5 paragraphs). After measuring the psychometric properties by means of internal consistency validity, and stability by Facronbach coefficient, and after analyzing the data, the study reached the following results: - That the study individuals agree with the desired) personal، moral، professional (qualities of the teacher in the School of Quality and Excellence
Attributes of personal, ethical and professional traits (cognitive, academic and educational) necessary for a teacher of the School of Quality and Excellence from their )point of view (an applied study)
مقال
Keywords: الصفات الشخصية، الصفات المهنية، الصفات الأخلاقية معلم مدرسة الجودة.; personal qualities, professional qualities, moral qualities, quality school teacher